ISLAMIC VALUES BASED STRATEGIC MANAGEMENT IN THE DEVELOPMENT OF EDUCATIONAL INSTITUTIONS - Fariha Rodliyana, Fara; Zaenul Fitri, Agus; Sulistyorini (International Journal of Multidisciplinary Reseach, 2025)
The dynamics of globalization, digitalization, and increasing quality competition require educational institutions to adopt strategic management that is adaptive and sustainable. However, in the context of Islamic educational institutions, strategic orientations that merely emphasize performance outcomes are often not fully aligned with Islamic values as the normative foundation of the institution. This study aims to examine the concept and urgency of Islamic values–based strategic management in the development of Islamic educational institutions. The focus of the study is directed toward the integration of Islamic values into the processes of strategy formulation, implementation, and evaluation. This research employs a qualitative library research method through critical analysis of scholarly literature, books, and relevant research findings on strategic management and Islamic values in education. The findings indicate that the implementation of Islamic values–based strategic management contributes to strengthening institutional identity, improving academic and non-academic quality, and supporting the sustainability of educational institutions. The integration of values such as amanah (trustworthiness), justice, musyawarah (consultation), and ihsan (excellence) is shown to be highly relevant as a foundation for strategic decision-making. Therefore, Islamic values–based strategic management can serve as a contextual and applicable alternative approach for the development of Islamic educational institutions amid global challenges.